Pendidikan Karakter Berbasis Tauhid-Tasawuf (Studi Penelitian Dayah Salafiyah Wilayah Barat Selatan Aceh) - Rahimi, Rahimi; Mukhlizar, Mukhlizar (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2024)
Santri or students, is the term for students in the world of Islamic boarding schools, students usually consist of two groups, namely santri mukim and santri kalong. Meanwhile, Islamic boarding school means an Islamic religious educational institution that grows and is recognized by the surrounding community with a dormitory system (complex) where the students receive education through a recitation system or madrasa which is completely under the sovereignty of the leadership of one or several kyai with unique characteristics. Charismatic and independent in all things. This research aims to find out what and how character education methods are applied to students at Islamic boarding schools, how learning about monotheism and Sufism at the Dayah Salafiyah Islamic boarding schools in the south-western region of Aceh is applied to the daily activities of students. This type of research is field research with a qualitative approach. To obtain the necessary data, the author used observation, interviews and documentation. The character education methods used in the boarding school are the mau'idoh khasanah method, teaching, the example method, the habituation method, getting up early, going home on time, sharing time, the tradition of hand kissing. When students are able to practice monotheism and Sufism well by carrying out the riyadhoh which has been taught through book study, one of which is Mukhtashor Ihya' Ulumuddin and accept and carry out the kiyai's advice well and supported by a boarding school environment that is close to the riyadhoh tradition, then good morals will automatically be formed.